O uso de atividades lúdicas como intervenção no binômio mãe filho com autismo e os efeitos nos níveis de ansiedade e estresse maternos - Souza, Vitor Brandão de (2023)
Objective: To assess the effects of regular playful activity shared between the motherchild binomial on the levels of maternal anxiety and stress of participants in the Adapted Physical Education Laboratory of the Federal University of Espírito Santo and develop a teaching technology in the form of a booklet on the importance of maintaining maternal health and mother-child interaction in the routine care of autistic children. Method: This is a quasi-experimental study, approved by the Ethics Committee on Research Involving Human Beings of the Health Sciences Center of the Federal University of Espírito Santo and approved under No. 5.285.734, with 11 binomials of autistic mother-child, the following instruments were used: sociodemographic form, IDATE and List of signs and symptoms of stress LSS/VAS. The interventions used were storytelling and history-making gymnastics. The data were analyzed with the IBM SPSS program version 24, with observed frequency, percentage, measures of central tendency and variability. The significance level adopted was 5%. We used the Wilcoxon test, which is a non-parametric hypothesis test, to compare two paired samples. Results: It can be stated that, in the first moment, the welcoming moment, there was no change in the anxiety state (p = 0.838); however, after the playful interventions, there was a statistically significant difference (p = 0.016, p = 0.029 and p = 0.041) for anxiety, as well as a significant decrease in stress signs and symptoms (p = 0.008). Conclusion: Playful activities based on children's storytelling and storytelling gymnastics proved to be effective in reducing anxiety and stress in mothers of autistic children. These results suggest that playful strategies may be a promising approach to assist mothers facing the daily challenge of caring for autistic children, providing benefits for the mothers' emotional well-being and potentially improving the quality of life of the family as a whole.